2012
DOI: 10.3892/ijmm.2012.1132
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mammalian MOR-1 gene expression after chronic treatment with morphine

Abstract: Morphine is an effective analgesic that acts by binding to the μ-opioid receptor (MOR) coded in the human by the OPRM1 gene. In the present study, we investigated the regulation of μ-opioid receptor (MOR-1) mRNA levels in all-trans-retinoic acid-differentiated SH-SY5Y human neuroblastoma cells under in vitro conditions with 10 μM morphine treatment for 24 h. In addition, we measured the MOR-1 levels in recombinant Chinese hamster ovary (CHO) cells, transfected with human μ-opioid receptor gene (hMOR) with 10 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The acute morphine exposure led to a significant increase in MOR expression in the SK‐N‐MC cell line, potentially enhancing sensitivity and binding or compensating for receptor internalization. However, chronic treatment resulted in a notable decline in MOR expression, aligning with prior research on human NB cells (SH‐SY5Y) 36 . This downregulation can be attributed to the activation of various MOR downstream pathways, such as Mitogen‐activated protein kinases (MAPK)/Extracellular signal‐regulated kinases (ERK), p38, and c‐Jun N‐terminal kinases (JNK), possibly through intermediaries like protein kinase A (PKA), protein kinase C (PKC), and Phosphoinositide 3‐kinases (PI3K) 37 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The acute morphine exposure led to a significant increase in MOR expression in the SK‐N‐MC cell line, potentially enhancing sensitivity and binding or compensating for receptor internalization. However, chronic treatment resulted in a notable decline in MOR expression, aligning with prior research on human NB cells (SH‐SY5Y) 36 . This downregulation can be attributed to the activation of various MOR downstream pathways, such as Mitogen‐activated protein kinases (MAPK)/Extracellular signal‐regulated kinases (ERK), p38, and c‐Jun N‐terminal kinases (JNK), possibly through intermediaries like protein kinase A (PKA), protein kinase C (PKC), and Phosphoinositide 3‐kinases (PI3K) 37 .…”
Section: Discussionsupporting
confidence: 83%
“…However, chronic treatment resulted in a notable decline in MOR expression, aligning with prior research on human NB cells (SH-SY5Y). 36 This downregulation can be attributed to the activation of various MOR downstream pathways, such as Mitogen-activated protein kinases (MAPK)/ Extracellular signal-regulated kinases (ERK), p38, and c-Jun N-terminal kinases (JNK), possibly through intermediaries like protein kinase A (PKA), protein kinase C (PKC), and Phosphoinositide 3-kinases (PI3K). 37 MAPK/ ERK, in particular, are deeply involved in drug-induced neuroadaptive changes, and specifically the progression of chronic morphine neuroadaptation.…”
Section: Differential Cellular Responses To Morphine Treatment and Ne...mentioning
confidence: 99%
“…This form of long-term plasticity in the brain requires relative stable changes in gene expression, which may alter neurotransmission and the structure of target neurons (McClung & Nestler, 2008 ; Robinson & Kolb, 2004 ). Recent studies have shown that the altered gene expression due to morphine exposure is responsible for behavioral changes in drug addicts (Prenus, Luscar, Zhu, Badisa & Goodman, 2012 ; Zhu, Badisa, Palm & Goodman, 2012 ). It has been shown that expression of many receptors and second messengers are affected by chronic morphine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that morphine selectively decreased MOR mRNA levels on peripheral CD4 + T cells, a result that deviates from those of previous studies ( Brejchova et al, 2020 ). However, one in vitro study ( Prenus et al, 2012 ) also confirmed that chronic morphine treatment leads to the downregulation of MOR gene expression, and the regulation of MOR gene expression is cell-type specific. Additionally, morphine did not affect the expression of KOR and DOR on either CD4 + T cells or CD8 + T cells.…”
Section: Discussionmentioning
confidence: 98%